2022
DOI: 10.3389/fpsyt.2022.845803
|View full text |Cite
|
Sign up to set email alerts
|

Family Resilience Scale Short Form (FRS16): Validation in the US and Chinese Samples

Abstract: Family resilience, which refers to the processes through which a family adapts to and thrives from adversities, has growing importance in recent years. In response to the need for further research on family resilience, the present research aims to abbreviate and validate Sixbey's Family Resilience Assessment Scale (FRAS) into a 16-item version Family Resilience Scale Short Form in the US (FRS16) and Chinese (FRS16_C) samples. The samples included 1,236 (Study 1) and 1,135 (Study 2) participants from the US and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 49 publications
1
18
0
3
Order By: Relevance
“…In the previous version (Gusarova, 2021), this scale did not pass the test, since in the original version it was focused mainly on a narrow (religious) understanding of spirituality, and not spirituality in the understanding of F. Walsh. Other researchers have also noticed this (Chiu, 2019;Chow, 2022;Gardiner, 2019).…”
Section: Resultsmentioning
confidence: 54%
“…In the previous version (Gusarova, 2021), this scale did not pass the test, since in the original version it was focused mainly on a narrow (religious) understanding of spirituality, and not spirituality in the understanding of F. Walsh. Other researchers have also noticed this (Chiu, 2019;Chow, 2022;Gardiner, 2019).…”
Section: Resultsmentioning
confidence: 54%
“…Higher scores on the ZBI indicate higher burden levels. The ZBI has demonstrated good reliability and validity in its English (Cronbach’s alpha: 0.90–0.92; validity: 0.40–0.80) and Chinese versions (Cronbach’s alpha: 0.88–0.94; validity: 0.67–0.77) 23 24. In this study, Cronbach’s alpha was 0.94.…”
Section: Methodsmentioning
confidence: 48%
“…Family resilience may include communication patterns, adaptation to change and social cohesion, familial roles, rituals, values, rules, role-modeling, parenting style, and intergenerational influences ( Duncan et al, 2021 ; Walsh, 2015 ). Formal assessments of family resilience can also be used for identification and strength-based therapeutic interventions (e.g., Family Resilience Short Form or Walsh Family Resilience Questionnaire; Chow et al, 2022 ; Walsh, 2015 ). Kerr et al (2021) found that despite increased negative feelings during the pandemic, parents felt closer to their children and had increased experiences of gratitude specific to parenting.…”
Section: Discussionmentioning
confidence: 99%